Factors Affecting the Learning of the Holy Quran among Severely and Profoundly Hearing-Impaired Children with a Cochlear Implant. - Mat Teh, Kamarul Shukri; Saari, Nur Hannah; Umat, Cila (2012)
The study aimed to examine three factors, namely self-factors, parental and teaching factors, which might affect the learning of the Arabic sounds used in the holy Quran among a group of Malay hearingimpaired children. This cross-sectional study involved fourteen severely and profoundly hearing-impaired children with a cochlear implant, aged between 8 to 15 years old, selected from those attending the Universiti Kebangsaan Malaysia Cochlear Implant Program. The duration of cochlear implant experience was between 5 to 10 years. All subjects used oral communication mode and attended normal mainstream schools. A set of questionnaires was adapted and subjects were interviewed directly to fill up this questionnaire. In addition, the children were also asked to read a surah in the holy Quran and these readings were rated by an expert in the recitation of the Quran. Bivariate Pearson correlation analyses revealed significant positive correlations between self-factors and teaching factors with the reading scores. However, parents’ factors were insignificant. Stepwise multiple linear regression showed that self-factors were the only significant predicting factor and contributed about 55.1% of the variance seen in the reading scores suggesting self-factors were most significant to facilitate the learning of the holy Quran among hearing-impaired children with a cochlear implant.